Tailored environments to study motile cells and pathogens - Muthinja, Mendi; Ripp, Johanna; Imle, Andrea; Haraszti, Tamás; Fackler, Oliver Till; Spatz, Joachim P.; Frischknecht, Friedrich (Cellular microbiology, 2018)
Abstract: Motile cells and pathogens migrate in complex environments and yet are mostly studied on simple 2D substrates. In order to mimic the diverse environments of motile cells, a set of assays including substrates of defined elasticity, microfluidics, micropatterns, organotypic cultures, and 3D gels have been developed. We briefly introduce these and then focus on the use of micropatterned pillar arrays, which help to bridge the gap between 2D and 3D. These structures are made from polydimethylsiloxane, a moldable plastic, and their use has revealed new insights into mechanoperception in Caenorhabditis elegans, gliding motility of Plasmodium, swimming of trypanosomes, and nuclear stability in cancer cells. These studies contributed to our understanding of how the environment influences the respective cell and inform on how the cells adapt to their natural surroundings on a cellular and molecular level.
Gesehen am 19.06.2019